PELATIHAN DAN SOSIALISASI BISNIS DIGITAL UNTUK MEMPERLUAS PASAR PADA PELAKU USAHA BATIK PALANGKA RAYA - Anike Retawati; Achmad Syamsudin (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to improve the understanding and skills of Palangka Raya Batik business actors in utilizing digital business as a strategy to expand the market. Batik business actors have an important role in maintaining local cultural identity while encouraging the growth of the region's creative economy. However, there are still various obstacles faced, such as limited understanding of digital marketing, the use of marketplaces, the creation of promotional content, business social media management, recording digital transactions, and online brand building strategies. The activity method uses a qualitative descriptive approach through observation, interviews, socialization, training, discussions, digital media use practices, and activity evaluation. Participants in the activity are Batik Palangka Raya business actors who have the potential to develop the market through digital platforms. The results of the activity show that training and socialization of digital business are able to increase participants' knowledge about the importance of digital branding, marketing through social media, marketplace utilization, digital payment use, and online consumer service strategies. This activity is expected to be able to encourage batik business actors to be more adaptive to the development of digital technology, expand market reach, and increase the competitiveness of local batik products in Palangka Raya.